Faktor penentu dan implikasi fenomena depopulasi komuniti Pulau Kecil di sekitar Mersing - Mustaffa Omar,; Marsitah Mohd Radzi,; Mohd Nasir Selamat,; Azima Abdul Manaf,; Mohd. Shamsudin,; Nor Jana Saim, (2011)
Community depopulation issue in Mersing is not a new phenomenon. However the root and the implication of the problems have not been given enough consideration. This paper draws attention to the seriousness of depopulation problem plaguing small islands around Mersing. An attempt to identify the underlying factors contributing to the problem, as well implications of the process of depopulation will be made. Strategic measures to overcome the above problem toward helping local authorities to develop those islands will be suggested